Rheological model of creep and relaxation in asphaltic mixtures using the transformed Carson Laplace, MAXIMA and Maple (2019)
In this article, the results of a creep and relaxation studies in asphalt mixtures are presented. Initially, a description of the conceptual model of the material and the details of the viscoelastic characterization in asphalt mixtures using the Creep test are shown. Then, the creep phenomenon is represented using a generalized Kelvin model with calibrated parameters [9]; also the relaxation model is developed using the direct and inverse transformation of Carson Laplace. For the modeling process of the two phenomena, a symbolic calculation code was programmed using MAXIMA-CAS and Maple software. Finally, we conclude that the generalized Kelvin rheological model fits the Creep laboratory data, and, the calculated relaxation function simulates the phenomenon correctly. This function was also compared with the approximate analytical model of Schapery (1965) and the result data were satisfactory. © 2006-2019 Asian Research Publishing Network (ARPN).